Case report: Reconstruction of a complex maxillofacial gunshot defect using a titanium patient-specific implant in a dog - Yang, Myungryul; Kang, Jinsu; Kim, Namsoo; Heo, Suyoung (Frontiers in Veterinary Science, 2022)
A 3-year-old male Wolf Shepherd was admitted for a large right facial defect with right nasal cavity exposure caused by a gunshot injury. Radiographic examination revealed severe loss of the right maxillary, nasal, and incisive bones, multiple fractures of both left and right palatine bones, and a comminuted fracture of the right mandible. Initial surgical procedure included computed tomography (CT) imaging for three-dimensional (3D) implant design. Open wound management was maintained for 18 days until the fresh granulation tissue fully covered the wound bed. The implant was designed in a ‘hand grasping shape’ to cover the defect, align multiple fractured palatine bones, and make a snap fit function. Multiple holes, including cortical screw holes, were added to the final design. The implant was printed on a titanium alloy. Surgical application of titanium PSI was performed 19 days after the primary surgery. A free sublingual mucosal graft was used to reconstruct the mucosal layer of the right nasal cavity. The mucosa was then covered with collagen membrane to strengthen the structure of the nasal cavity. Blunt dissection of the hard palate mucoperiosteum above the palatine process and palatine bones, soft tissue above the maxilla was performed, and the 3D printed titanium implant was fastened in a preplanned position. The facial soft tissue defect was reconstructed, and the titanium PSI was covered using an angularis oris cutaneous flap. Partial flap necrosis occurred in the rostral aspect, and the wound was managed to heal by a second intension. Flap dehiscence at the junction of the flap and hard palate mucoperiosteum occurred with exposure of the implant two days postoperatively. Multiple attempts to close the defect failed, and the owner wanted to stop treatment. Healthy granulated tissue was observed proximal to the implant. The defect no longer increased in size and did not show any noticeable complications related to the defect at 60 days after titanium PSI application, and the dog was discharged. Six months post-operatively, the dog remained active with great appetite, gained weight, and showed acceptable facial symmetry without enlargement of the implant exposure or any implant-related problems.